Acoustic spin skyrmion molecule lattices enabling stable transport and flexible manipulation - Liu, Lei; Zhang, Xiujuan; Lu, Ming-Hui; Chen, Yan-Feng (Nature communications, 2025)
Skyrmions—topologically protected nanoscale spin textures with vortex-like configurations—hold transformative potential for ultra-dense data storage, spintronics and quantum computing. However, their practical utility is challenged by dynamic instability, complex interaction, and the lack of deterministic control. Here, we introduce a skyrmion molecule lattice, a novel architecture where pairs of skyrmions with opposite polarizability are symmetry-locked into stable molecule configurations. These molecules emerge as propagating eigenstates of the system, enabling robust transport. Using a boundary engineering technique, we achieve deterministic control over skyrmion creation, deformation, annihilation, and polarizability inversion. This is experimentally demonstrated in a graphene-inspired acoustic surface wave metamaterial by harnessing topological acoustic spin structures. Our work, leveraging symmetry principles, establishes a universal framework for stabilizing, transporting and manipulating the skyrmion quasiparticles. The authors introduce a skyrmion molecule lattice, where pairs of skyrmions with opposite polarizability are symmetry locked into stable molecule configurations. The authors achieve deterministic control over skyrmion creation, deformation, annihilation, and polarizability inversion.